2022
DOI: 10.1590/s1980-657420220010821
|View full text |Cite
|
Sign up to set email alerts
|

Postural control in football players with vision impairment: Effect of sports adaptation or visual input restriction?

Abstract: To assess the postural control performance of football 5-a-side (FFS) players, comparing them with sighted players. Methods: Eight FFS players and 7 sighted futsal players were included. Postural control tests included feet together stance (FTS) and single-leg stance (SLS) tasks, performed on rigid and foam surfaces. Sighted players performed the tests with open (EO) and closed (EC) eyes. Area of displacement (Area) and average velocity (Vavg) were calculated from the center of pressure time-series coordinates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
(56 reference statements)
2
2
0
Order By: Relevance
“…Similar findings were found among young football players; significant increases in conventional COP parameters were observed only when standing on a foam pad in a one-leg stance with EC [54]. These results might indicate that young and healthy adults can compensate for a disturbed/loss of vision when somatosensory and vestibular input remain unaltered by adapting and reweighting the sensory input processing [54,57]. Indeed, it has been shown that the process of reweighting visual and somatosensory inputs reaches optimal performance in adulthood [62].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar findings were found among young football players; significant increases in conventional COP parameters were observed only when standing on a foam pad in a one-leg stance with EC [54]. These results might indicate that young and healthy adults can compensate for a disturbed/loss of vision when somatosensory and vestibular input remain unaltered by adapting and reweighting the sensory input processing [54,57]. Indeed, it has been shown that the process of reweighting visual and somatosensory inputs reaches optimal performance in adulthood [62].…”
Section: Discussionsupporting
confidence: 83%
“…Even when analyzing RI under distorted visual input when wearing stroboscopic glasses, young adults were able to maintain their balance; however, when an additional sensory input was challenged by standing on a foam pad (somatosensory input), RI indices in all evaluated COP parameters increased [57]. Similar findings were found among young football players; significant increases in conventional COP parameters were observed only when standing on a foam pad in a one-leg stance with EC [54]. These results might indicate that young and healthy adults can compensate for a disturbed/loss of vision when somatosensory and vestibular input remain unaltered by adapting and reweighting the sensory input processing [54,57].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations